Sex-related differences in exercise performance and outcome of patients with hypertrophic cardiomyopathy. (1st November 2020) - Ghiselli, Luca; Marchi, Alberto; Fumagalli, Carlo; Maurizi, Niccolò; Oddo, Andrea; Pieri, Francesco; Girolami, Francesca; Rowin, Ethan; Mazzarotto, Francesco; Cicoira, Mariantonietta; Ribichini, Flavio; Arretini, Anna; et al.
Abstract : Aims: Exercise performance is known to predict outcome in hypertrophic cardiomyopathy (HCM), but whether sex-related differences exist is unresolved. We explored whether functional impairment, assessed by exercise echocardiography, has comparable predictive accuracy in females and males with HCM. Methods: We retrospectively evaluated 292 HCM patients (46 ± 16 years, 72% males), consecutively referred for exercise echocardiography; 242 were followed for 5.9 ± 4.2 years. Results: Peak exercise capacity was 6.5 ± 1.6 metabolic equivalents (METs). Sixty patients (21%) showed impaired exercise capacity (≤5 METs). Exercise performance was reduced in females, compared with males (5.6 ± 1.6 vs 6.9 ± 1.5 METs, p < 0.001; peak METs ≤ 5 in 40% vs 13%, p < 0.001), largely driven by a worse performance in women >50 years of age. At multivariable analysis, female sex was independently associated with impaired exercise capacity (odds ratio: 4.67; 95% confidence interval (CI): 1.83–11.90; p = 0.001). During follow-up, 24 patients (10%) met the primary endpoint (a combination of cardiac death, heart failure requiring hospitalization, sustained ventricular tachycardia, appropriate implantable cardioverter defibrillator discharge, resuscitated sudden cardiac death and cardioembolic stroke). Event-free survival was reduced in females ( p = 0.035 vs males). Peak METs were inversely related to outcome in males (hazard ratio (HR) per unit increase: 0.57; 95% CI: 0.39–0.84; p = 0.004) but not in females (HR: 1.22; 95% CI: 0.66–2.24; p = 0.53). Conclusions: Female patients with HCM showed significant age-related impairment in functional capacity compared with males, particularly evident in post-menopausal age groups. While women were at greater risk of HCM-related complications and death, impaired exercise capacity predicted adverse outcome only in men. These findings suggest the need for sex-specific management strategies in HCM.